The Consistency of Munāsabah Application in Tafsīr Al-Mishbāh: A Structural Analysis of Surah Al-Baqarah and Āli 'Imrān - Laeli Saputri; Siti Asiah; Siti Maryam (Lembaga Yasin AlSys, 2026)
The principle of munāsabah is central to understanding the structural relationships, continuity of meaning, and textual coherence of the Qur’an. This study analyzed the methodological construction and application of munāsabah in M. Quraish Shihab’s Tafsir Al-Misbah, focusing on textual and thematic analyses of Surah Al-Baqarah and Surah Āli ‘Imrān. A qualitative descriptive library-research design was employed, integrating thematic exegesis (mawḍūʿī), qualitative content analysis, and a hermeneutical–exegetical perspective. The findings indicate that Quraish Shihab positions munāsabah as a fundamental hermeneutical instrument for demonstrating the organic unity of the Qur’anic text (waḥdah al-Qurʾāniyyah). Two principal typologies were identified: five models of correspondence between verses and eight models of correspondence between surahs. The verse-level models encompass relationships among verses within a surah, between verses and their conclusions, among sentences, among words, and between the opening and closing verses of a surah. The surah-level models include relationships between adjacent surahs, between the opening and conclusion of a surah, between a surah’s name and its central theme, between one surah’s conclusion and the next surah’s opening, and between fawātiḥ al-suwar and the surah’s substantive content. The analysis further demonstrates consistent thematic integration between Al-Baqarah, as a foundation of sharia and faith, and Āli ‘Imrān, as a reinforcement of monotheistic argumentation and steadfastness amid social contestation. By combining the taḥlīlī method with an adabī al-ijtimāʿī orientation, Quraish Shihab connects classical linguistic analysis with contemporary social concerns. This approach contributes to Qur’anic coherence studies by offering a systematic alternative to atomistic interpretation and presenting revelation as an integrated, contextually relevant, and solution-oriented discourse.